Fluid Inclusions and H-O-C-S Isotopes of the Wushan Copper Polymetallic Deposit in the Suizao Area, Hubei Province: Implications for Ore Genesis - Pan-Pan Niu; Shao-Yong Jiang; Suo-Fei Xiong; Qi-Sheng Hu; Tian-liang Xu (Geofluids)
The Wushan copper polymetallic deposit is located in the Tongbai-Dabie orogenic belt in central China. Two small granitoid stocks (Donggushan and Xigushan) occur in the deposit, which is next to the largest Qijianfeng Granite Complex in the Suizao area. The mineralization of Wushan copper polymetallic deposit is mainly composed of ore-bearing quartz veins and quartz stockworks. Two hydrothermal stages are identified as the quartz-sulfide stage (early stage) and the barren quartz stage (late stage). A detailed petrographic study shows four types of fluid inclusions in quartz, including the aqueous fluid inclusions (L+V/V+L), the aqueous-carbonic fluid inclusions (L+V+CO2), the pure carbon dioxide fluid inclusions (pure CO2), and the daughter mineral-bearing multiphase fluid inclusions (S). The daughter mineral-bearing multiphase fluid inclusions (S) are further divided into three subclasses according to their different solid mineral assemblages, including (1) S1: L+V+Hal, (2) S2: L+V+CO2+S (chalcopyrite), and (3) S3: L+V+S (calcite, chalcopyrite, and hematite)±Hal. A laser Raman spectroscopic analysis shows that the main components of fluid inclusions are water and carbon dioxide. The solid minerals of the S-type fluid inclusions include halite, calcite, chalcopyrite, and hematite. The homogenization temperatures of fluid inclusions are 377 to 468°C for the early stage, with a salinity of 11.1 to 34.1 wt.% NaCl equivalent (11.1 to 17.4 wt.% NaCl equivalent and 28.4 to 34.1 wt.% NaCl equivalent, respectively) and an estimated pressure of 89 to 137 MPa. The homogenization temperatures of fluid inclusions in the late stage are 267 to 380°C with salinity of 7.0 to 12.1 wt.% NaCl equivalent and an estimated pressure of 46 to 115 MPa. Therefore, the temperature, salinity, and pressure of the fluid show a decreasing trend from the early to the late stage. In the early stage, the fluid is immiscible, which leads to the precipitation of sulfides. Pyrite shows a δ34S of approximately 0 (-1.8 to +3.4‰), and chalcopyrite also shows a similar δ34S of approximately 0 (+1.5 to +2.4‰), which indicates that the sulfur in the ore-forming fluid is mainly derived from deep-seated magma. Combined with C-H-O isotopic compositions, the initial ore-forming fluid is likely magmatic water, but with the addition of meteoric water in the late stage. By comparing with the typical characteristics of magmatic hydrothermal vein deposit and orogenic deposit related to shear zones, we suggest that the Wushan copper polymetallic deposit is most likely a magmatic hydrothermal vein deposit, which is of great significance for the further exploration work in the Wushan and surrounding areas. This new finding also fills the gap that no magmatic hydrothermal vein type Cu deposits have been found in the Suizao area or even in the Qinling-Dabie orogenic belt in central China.